Quantitative T2 Mapping Shows Increased Degeneration in Adjacent Intervertebral Discs Following Kyphoplasty. (April 2020) - Pachowsky, Milena L.; Kleyer, Arnd; Wegener, Lisa; Langenbach, Andreas; Simon, David; Janka, Rolf; May, Matthias; Welsch, Goetz H.
Objective: A minimally invasive treatment of osteoporotic and nonosteoporotic thoracic and lumbar spine fractures is cement augmentation (kyphoplasty). Little is known about the impact on adjacent intervertebral discs. A quantitative magnetic resonance imaging (MRI) approach in addition to morphological MRI is desirable to evaluate changes in the intervertebral disc. Our study aims to evaluate the feasibility of T2 mapping for the detection of subtle changes in the intervertebral discs in spines after kyphoplasty. Design: Intervertebral discs were assessed by quantitative MRI (3.0 T) using T2 relaxation time mapping. Region of interest (ROI; 6 per disc) analyses were performed. The ROIs at the anterior and posterior edges were interpreted as annulus fibrosus (AF). The 2 very inner zones were regarded as nucleus pulposus (NP) and the regions in between as intermediate transition zone. We compared T2 relaxation time values of intervertebral discs adjacent to the vertebrae after kyphoplasty with those nonadjacent to vertebrae after kyphoplasty, especially in the NP. Results: The analysis of the ROIs showed that the intervertebral discs of the adjacent vertebral segments are associated with reduced T2 values compared to those that are nonadjacent to the affected vertebrae. Conclusion: This study is to our knowledge the first investigation of intervertebral discs after kyphoplasty by quantitative MRI. Quantitative T2 mapping shows increased degeneration in adjacent intervertebral discs following kyphoplasty. Besides its contribution to a broader knowledge of postoperative changes after kyphoplasty, our findings may help to improve differentiation between healthy and degenerated intervertebral discs using these techniques.